2019
DOI: 10.1089/pop.2018.0094
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Care Coordination Among Children with Special Health Care Needs

Abstract: Socioeconomic disparities in access to care coordination have been noted among children with special health care needs (CSHCN). Following recent policy developments and technological innovation, care coordination has become more widespread, possibly leading to reduced disparity in care coordination access. This study investigates whether child and household characteristics remain associated with unmet need for care coordination among CSHCN. CSHCN (aged <18 years) requiring ‡2 types of health services in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…This period was selected to provide comparable data to previous studies in which authors evaluate 12-month health services use among children with chronic health conditions. 7,9,10 Total costs of care (including both acute and nonacute care visits to facilities in the hospital system) were determined over the same period by combining direct and indirect costs over this period. Direct costs, both fixed and variable, are those costs attributed to the patient encounter that are 20) -…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This period was selected to provide comparable data to previous studies in which authors evaluate 12-month health services use among children with chronic health conditions. 7,9,10 Total costs of care (including both acute and nonacute care visits to facilities in the hospital system) were determined over the same period by combining direct and indirect costs over this period. Direct costs, both fixed and variable, are those costs attributed to the patient encounter that are 20) -…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, authors found that 14% of US children with SHCNs had unmet needs for care coordination. 7 For children admitted to the hospital, the discharge process offers a unique opportunity to initiate coordination of follow-up care and prevent readmissions or ED revisits. 8 At this university-affiliated medical center, a tertiary-care regional hospital, the Center for Children with Complex and Chronic Conditions (C5) program was established in 2008 to initiate care coordination for children with CCCs in an inpatient transitional care unit and continue this coordination in a multidisciplinary outpatient C5 clinic, with home visits by a designated care coordination team.…”
mentioning
confidence: 99%
“…Such initiatives can be a cornerstone of addressing the unmet need for care coordination identified among children with special health care needs in nationwide population-based surveys. 23 The results from our study suggest that development of new care coordination programs and expansion of existing programs should prioritize improving outpatient follow-up visit completion among children with prolonged hospitalizations and children who had been admitted to the ICU. Our conclusions are limited by several aspects of the data and study design.…”
Section: Discussionmentioning
confidence: 77%
“…Infants with medical and developmental complexity require care from multiple sources and in many settings [ 14 ]. Access to medical, developmental, and care coordination services is not always a given, particularly for children whose families face social or economic disadvantage, have limited English proficiency, or live in rural areas [ 15 , 16 ]. Some high-risk infant follow-up programs have addressed barriers to, and inequities in, access to care through innovative delivery models.…”
Section: Discussionmentioning
confidence: 99%